A global model of tropospheric chlorine chemistry: Organic versus inorganic sources and impact on methane oxidation - Hossaini, Ryan (2016)
Chlorine atoms (Cl) are highly reactive toward hydrocarbons in the Earth’s troposphere, including the greenhouse gas methane (CH4). However, the regional and global CH4 sink from Cl is poorly quantified as tropospheric Cl concentrations ([Cl]) are uncertain by ~2 orders of magnitude. Here we describe the addition of a detailed tropospheric chlorine scheme to the TOMCAT chemical transport model. The model includes several sources of tropospheric inorganic chlorine (Cly), including (i) the oxidation of chlorocarbons of natural (CH3Cl, CHBr2Cl, CH2BrCl, and CHBrCl2) and anthropogenic (CH2Cl2, CHCl3, C2Cl4, C2HCl3, and CH2ClCH2Cl) origin and (ii) sea-salt aerosol dechlorination. Simulations were performed to quantify tropospheric [Cl], with a focus on the marine boundary layer, and quantify the global significance of Cl atom CH4 oxidation. In agreement with observations, simulated surface levels of hydrogen chloride (HCl), the most abundant Cly reservoir, reach several parts per billion (ppb) over polluted coastal/continental regions, with sub-ppb levels typical in more remote regions. Modeled annual mean surface [Cl] exhibits large spatial variability with the largest levels, typically in the range of 1-5×104 atoms cm-3, in the polluted northern hemisphere. Chlorocarbon oxidation provides a tropospheric Cly source of up to ~4320 Gg Cl/yr, sustaining a background surface [Cl] of <0.1 to 0.5 × 103 atoms cm-3 over large areas. Globally, we estimate a tropospheric methane sink of ~12-13 Tg CH4/yr due the CH4 + Cl reaction (~2.5% of total CH4 oxidation). Larger regional effects are predicted, with Cl accounting for ~10 to >20% of total boundary layer CH4 oxidation in some locations.